Pelatihan Google Bisnisku Untuk Meningkatkan Pemasaran Pada Karang Taruna Tunas Mandiri Desa Sukaharja - Agustiena Merdekawati; Andrie Kurniawan; Henny Leidiyana; Al Ghazali; Waryono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
One way to market and promote sales products can be through online media such as websites, marketplaces, Google My Business, Instagram, Facebook and the currently famous TikTok. Google my business is a medium that can help marketing to promote products. Tunas Mandiri youth organizations are located in Sukaharja village, Ciomas, Bogor. Many of the youth organizations have businesses or production and the Tunas Mandiri youth organizations also open up business fields for the community to improve their economy. However, the current marketing and promotions are still less effective, so we need a medium like Google My Business, but there are still many of them who don't understand about Google My Business, such as: (1) Members of the Tunas Mandiri youth organization do not understand the use of web browser applications or the Google browser. (2). Most members of the Tunas Mandiri youth group are not familiar with Google My Business. (3) Some members of the Tunas Mandiri youth organization who are familiar with Google My Business, still don't understand how to manage a business that will be displayed on Google searches, maps, edit business information (for example, address, phone number, and opening hours). Therefore, the Google My Business training is held in the hope that it can make marketing and promotion easier and can reduce operational costs.